2023
DOI: 10.2147/vhrm.s396295
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Nigella sativa and Ginger as Appetite Suppressants: An Experimental Study on Healthy Wistar Rats

Abstract: Background Obesity is a global pandemic that is associated with high morbidity and mortality. Natural herbs are commonly used for weight reduction and appetite suppression. Therefore, we aim to investigate the role and mechanism of Nigella sativa (NS) and ginger on weight reduction and appetite regulation. Methods This experimental study was performed at Imam Abdulrahman Bin Faisal University. Twenty-five female rats were distributed into 5 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Furthermore, the effect could be mediated via the signalling of the hormone leptin in the satiety centre of the brain, leading to hypophagic effects and subsequent weight loss in experimental animals [ 70 ]. Previous research has also reported that consuming NS could lead to an increase in ghrelin, one of the peptides that regulate appetite [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the effect could be mediated via the signalling of the hormone leptin in the satiety centre of the brain, leading to hypophagic effects and subsequent weight loss in experimental animals [ 70 ]. Previous research has also reported that consuming NS could lead to an increase in ghrelin, one of the peptides that regulate appetite [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ginger has regulated the lipid profile by decreasing total cholesterol and enhancing HDL. In addition, ginger can affect some of the peptides involved in appetite stimulation, such as the increase in ghrelin (42). Diet-induced obesity with hypothalamic leptin resistance interferes with the homeostatic control of body weight and appetite.…”
Section: Discussionmentioning
confidence: 99%
“…Given the well-established association between obesity and various non-communicable diseases, such as Coronary Heart Disease, Diabetes Mellitus Type 2, Hypertension, and Stroke, it is imperative to emphasize the necessity of preventative interventions targeting obesity. 1 , 2…”
Section: Dear Editormentioning
confidence: 99%
“…Given the well-established association between obesity and various non-communicable diseases, such as Coronary Heart Disease, Diabetes Mellitus Type 2, Hypertension, and Stroke, it is imperative to emphasize the necessity of preventative interventions targeting obesity. 1,2 Based on the background, it is mentioned that Nigella sativa and ginger are herbs used as anti-obesity, so it would be nice if the research is carried out in accordance with the research objectives, namely to determine the effect of consumption of Nigella sativa and ginger to lose weight and suppress appetite. According to our thinking, it would be nice to use obese animals so that weight loss can be known due to consumption of the two herbs.…”
mentioning
confidence: 99%